Data‐Driven Approach for Improving Asset Reliability. Issue 4 (3rd April 2019) - Jalla, Srinivas; Davis, Clinton
Abstract : Numerous asset management issues were addressed when a water utility studied the practices of successful cohorts and used data analytics to change its processes and organizational structure for the better.